Structural and optical investigation of CdSe quantum dots - Dipesh, Neupane (Kathmandu University Journal of Science, Engineering and Technology, 2013)
CdSe semiconducting Quantum dots were prepared by a chemical method at a room temperature. X-ray powder diffraction and transmission electron microscope measurements conformed a hexagonal cubic crystalline phase of Cdse semiconducting Quantum dots of about 15 nm average size with nearly spherical shape. The absorption and photoluminescence spectra of the CdSe quantum dots were strongly shown blue shifted due to size quantization. The present study describes a simultaneous and highly reproducible large scale synthesis of highly luminescent CdSe Quantum dots. Kathmandu University Journal of Science, Engineering and Technology Vol. 8, No. II, December, 2012, 83-88 DOI: http://dx.doi.org/10.3126/kuset.v8i2.7329